FUNGSI BAHASA SANTRI WANITA DALAM KOMUNIKASI DI PESANTREN - Eka Susylowati; Rahmat Wisudawanto (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2021)
The aim of the study to describe the functions of language in communication of the female santri of Takhashushiyyah Schools at Assalaam Islamic Modern Boarding School and Islam Al-Mukmin Boarding School of Ngruki, Sukoharjo Regency. They were collected through observation, recording, listening, note-taking, and in-depth interview. The result shows that the languages or codes in both boarding schools function as the media to convey the sense of solidarity, to establish intimacy among speakers and addressees, to introduce themselves, to convey their intents, and to show their identity, as opening and closing language in religious activities and language of teaching and learning interactions, and as language for foreign language training of the santri, as language of intimacy, gossiping, and identity, as language of unity, functioned for quoting and emphasizing the contents of messages, as language habit and for admiration, information-delivery, prestige impression, preserving local language, creation of religious impression, intimacy, reference, and respect